Anxiety, Boredom, and Burnout Among EFL Teachers: The Mediating Role of Emotion Regulation - Shen, Guorong (Frontiers in Psychology, 2022)
Teachers’ emotions are explicitly and conceptually presented as part of an educational system that affects and is affected by learner upshots, namely, learners’ self-emotions, behaviors, and cognition since educators and learners are involved in the outcomes of the school setting. EFL educators recurrently experience emotional damages during involvement in their profession as burnout, stress, boredom, and anxiety. EFL teachers need to regulate their emotions when facing a multivariate class environment that provides each learner with undeniable uniqueness. The subject of the relationship between emotion regulation and the teacher's emotions is receiving increasing attention in research. EFL teachers should be provided with an emotional regulation strategy to have a positive learning-instructing effect in the entire school community as fun learning activities, energetic students, enthusiastic educators, and strong relationships between the board of education. To focus on the role of teachers’ emotion on the one hand and the mediator role of emotional regulation, on the other hand, the current study endeavored to review the role of emotional regulation strategies more intensely to decrease negative emotions. Finally, some educational suggestions of the study regarding the educators’ behaviors are pinpointed.